General survey on the epidemic hydatidosis in Equidae - Younis, Khalida Hussain (The Iraqi Journal of Veterinary Medicine, 2010)
A general survey was implemented on the hydatid cyst disease in Equidae duing the period from 1\11\2001 till 31\10\2002. The results showed that the infection rate was 7.8% by examining 242 animals, 156 males and 86 females. The rate of hydatid cysts infection reached 8.3% in males and6.97%in females. The livers were the most infected organ by parasitic rate of 68.42% ,in livers and lungs together was 26.31% while in lung was 5.26%.A198 hydatid cysts were isolate from donkeys livers with rate of 59.59%, from livers and lungs with rate of 38.33% while the isolation rate from lung was 1.5% .The fertility rate of hydatid cysts in livers reached 50% , most of them were in the examined infected organs reached 11.86% . Fertile hydatid cysts where found near sterile or calcified or caseated cysts in the same infected organ.